Ireland and Anglo-American Relations 1899-1921 - Ward, Alan J. (University of Toronto Press, 1969)
The years from the Boer War to the establishment of the Irish Free State were crucial not only for political developments in Ireland itself but also for the effect these had in Britain and America. A comprehensive picture is given in this book of the part Ireland played in the conduct of Anglo-American relations. The author draws on new data from archives in all three countries to give a unique account of the influence which an immigrant minority can exercise over the policies of a major nation: the United States. New light is shed on many of the events of the period, including the role of the Boer war in Anglo-American relations and the whole question of co-operation between Britain and the United States during the First World War. New information is also revealed about Irish internal affairs: the Easter Rising, the execution of Sir Roger Casement, and the partition of Ireland. As a case study the book illustrates how complex is the interplay between domestic and international politics and, in particular, how important the activities of an immigrant pressure group can be in world affairs
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jul 2019)
Keywords: POLITICAL SCIENCE / International Relations / General; Irish Americans; Geschichte; USA; Großbritannien; Irland